The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1111/j.1752-7325.2011.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health among white, black, and Mexican-American elders: an examination of edentulism and dental caries

Abstract: Objectives To examine racial/ethnic disparities in oral health among older Americans. Methods Differences in frequency of edentulism and number of decayed, missing, and filled teeth were assessed in 2,679 non-Hispanic white, 742 non-Hispanic black, and 934 Mexican-American individuals aged 60 and older from the National Health and Nutrition Examination Survey (1999-2004). Results Controlling for potential confounding variables, blacks and Mexican-Americans had significantly higher numbers of decayed teeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(93 citation statements)
references
References 21 publications
7
81
1
3
Order By: Relevance
“…On the other hand, Celeste and Nadanovsky [28] showed that among adults a longer time since last dental visit was associated with dental caries; also unmet dental need was related to presence of caries in a rural Indian fishing community [29], corroborating our results. Although the variable smoking status was not contemplated in the present study, smoking was associated with a greater number of decayed teeth in blacks and MexicanAmericans, [26] nevertheless, Colombia has one of the lowest prevalence of smoking in Latin America [30,31] and this fact could not affect the frequency on SRDC in the present study. Besides, smoking is more associated with oral cancer, periodontitis and worst wound healing [32,33].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…On the other hand, Celeste and Nadanovsky [28] showed that among adults a longer time since last dental visit was associated with dental caries; also unmet dental need was related to presence of caries in a rural Indian fishing community [29], corroborating our results. Although the variable smoking status was not contemplated in the present study, smoking was associated with a greater number of decayed teeth in blacks and MexicanAmericans, [26] nevertheless, Colombia has one of the lowest prevalence of smoking in Latin America [30,31] and this fact could not affect the frequency on SRDC in the present study. Besides, smoking is more associated with oral cancer, periodontitis and worst wound healing [32,33].…”
Section: Discussionmentioning
confidence: 75%
“…This result suggests that contextual factors affect SRDC. Contextual consequences were also observed for dental caries in several studies [13,14,23,24,26].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For this reason, some authors prefer to consider social injustice as a criterion of the difference between inequality and inequity. 14 There is broad knowledge on social determination, inequality and inequity, 16,17,18,19,20,21 yet there is little or no discussion on inequity and social justice. These should guide a discussion based on the principles of rightness, such as distributives of social justice (principle of right, merit and need) 22 or principles of social justice (guarantee of freedom, equitable equality of opportunities and presence of inequalities only to favor the disfavored).…”
Section: Health Promotionmentioning
confidence: 99%